Simulation of Subcritical Experimentsin ZED-2 using G4-STORK - Mahzooni, Salma (My University, 2015)
In nuclear reactors, transients may happen, for example at the time of refueling, rod withdrawals or insertions, and during reactor accidents. Transient behavior may result from changes either in materials or in the geometry of the reactor core components. An enhanced understanding of these time-dependent changes in reactors may improve the reactor operation and reduce the probability of accidents. In spite of the importance of understanding the conditions that lead to transients, there are not many time-dependent reactor simulation codes available. This study is focused on modeling the sub-critical reactivity measurements in the ZED- 2 reactor, using the recently developed G4STORK computer code. The ZED-2 experiment measures the sub-critical state resulting from a step-wise reduction of the moderator level. G4-STORK is a time-dependent Monte Carlo code for reactor neutronics calculations based on the GEANT4 toolkit. G4-STORK has the ability to follow the evolution of the neutron population in time, including delayed neutrons, and to model the resulting changes in material and geometric properties of a reactor. The keff values calculated by G4-STORK were compared with the experimental measurements and with MCNP results. The comparison shows significant discrepancies with both MCNP and the experimental measurements. These discrepancies are increasing as the reactor becomes increasingly subcritical (from ∼20 mk to ∼40 mk). The recently developed G4-STORK code is still at an early stage of its development, and needs to be improved further to be used for transient analyses of the reactors. Given the flexibility of G4-STORK, there are many opportunity to improve and extend this code.